Depth of the Stable Atmospheric Boundary Layer over a Shallow Uniform Slope - Maguire, Andrew James; Rees, Julia Margaret; Derbyshire, Stephen Hal (Física de la Tierra, 2008)
This paper is concerned with the depth of the stably stratified atmospheric boundary layer overlying a shallow uniform slope. A specified surface heat flux is applied. Large eddy simulation modelling is used to compare the boundary layer depths predicted by three different definitions for the depth of the stable layer that are in common use: the height at which the heat flux has dropped to 5% of its surface value, the height at which the Zilitinkevich ratio is a prescribed constant value, and, thirdly, the height at which the wind speed reaches its maximum value. These three definitions are based on different physical properties. Results from both one-dimensional (in the sense that span-wise spatial derivatives are all assumed to be zero but the three components of the velocity field are included) and fully threedimensional simulations are presented. Key findings from this study indicate that in the onedimensional simulations, cross-slope winds could adversely affect the surface layer statistics leading to the prediction of an overly shallow boundary layer. This problem was alleviated in the threedimensional simulations. This suggests that fully three-dimensional simulations are required for stable boundary layers over sloping terrain.